Molecule Recognition and Release Behavior of Naphthalenediimide Derivative via Supramolecular Interactions. Issue 7 (27th January 2021) - Ma, Yudong; Luo, Lixing; Yang, Canglei; Wang, Wei; Liu, Xitong; Zhang, Jing; Huang, Wei
Abstract: Self‐assembled charge‐transfer complexes based on supramolecular interactions have attracted immense research interest due to their unique packing and (opto)electronic applications. Herein, two new binary cocrystals with a similar 1:1 mixed‐stack arrangement are synthesized by solvent evaporation or grinding method using N, N ′‐dimethyl‐1, 4, 5, 8‐naphthalene tetracarboxylic diimide (Me‐NDI) as the receptor. Single‐crystal X‐ray diffraction analysis confirms the successful molecular‐level recognition and various weak interaction networks. Upon thermal treatment of 1, 4, 8, 11‐tetramethyl‐6, 13‐triethylsilylethynyl pentacene (TMTES‐P)/Me‐NDI complex, in situ cocrystal‐to‐crystal conversion is observed, and the receptor is gradually released, while the perylene/Me‐NDI cocrystal disassembles in the same manner as a single‐component compound. The aligned short‐contact network, good stability of TMTES‐P, and anisotropic attachment energies of the TMTES‐P/Me‐NDI cocrystal disassemble in a manner same to that of a single‐component compound. The aligned short‐contact network, good stability of TMTES‐P, and anisotropic attachment complexes are believed to promote the release of specific molecules. These structure–property relationship results provide new insights into the design of a supramolecular class with desired functionalities in terms of self‐assembled recognition, release, or crystal conversion. Abstract : Two novel host–guest complexes based on Me‐NDI receptor are successfully prepared. Upon thermal treatment, TMTES‐P/Me‐NDI complex reveals an in situ cocrystal to crystal conversion and gradual receptor release behavior, while perylene/Me‐NDI cocrystal disassembles like a single‐component compound. Short‐contact network and anisotropic attachment energies play a vital role in the thermal decomposition process.